Beta derivative applied to dark and singular optical solitons for the resonance perturbed NLSE - Yusuf, Abdullahi; İnç, Mustafa; Aliyu, Aliyu Isa; Baleanu, Dumitru (Springer Heidelberg, 2019)
In this research we obtain some dark and singular solitons for the resonance perturbed nonlinear Schrodinger equation (NLSE) with beta derivative (BD). Two well-known analytical approaches have been utilised to extract the results. The constraints conditions are stated for the well-being and existence of the results. Some figures have been plotted to demonstrate the physical behavior of the obtained solutions.
Keywords: General Fractional Derivatives; Partial-Differential-Equations; Conservation-Laws; Cahn-Allen; Model; Disease